2008 34th European Conference on Optical Communication 2008
DOI: 10.1109/ecoc.2008.4729420
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of high spectral efficient OFDM-QAM long reach passive optical network

Abstract: We demonstrate a high spectral-efficient LR-PON using 4Gb/s OFDM-QAM for both up-anddownstream, achieving a high split-ratio 256, using optical components optimized for GPON.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 2 publications
(2 reference statements)
0
10
0
Order By: Relevance
“…Therefore, aggregate data of several Gbps can travel much longer distances without the need for dispersion compensating modules and with high split ratios [2], [3], while other works have shown that OFDM signals are more robust to Rayleigh backscattered light than NRZ signals used in typical PON architectures [7]. Consequently a larger user base can be covered by each CO reducing the cost of deployment and maintenance of COs and distant users can easily be covered.…”
Section: Physical Layer Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, aggregate data of several Gbps can travel much longer distances without the need for dispersion compensating modules and with high split ratios [2], [3], while other works have shown that OFDM signals are more robust to Rayleigh backscattered light than NRZ signals used in typical PON architectures [7]. Consequently a larger user base can be covered by each CO reducing the cost of deployment and maintenance of COs and distant users can easily be covered.…”
Section: Physical Layer Aspectsmentioning
confidence: 99%
“…Recently OFDM(A) has also been making its way into the optics world, both in core [1], and access networks. In the latter case, studies have proven that OFDM can provide high capacity, long-reach and cost-effective operation for PONs [2], [3]. The use of OFDM in optical access networks has mainly been driven by the necessity to increase transmission rates without increasing the bandwidth of optoelectronic transceivers, as opposed to focusing on link optimization.…”
Section: Introductionmentioning
confidence: 99%
“…OFDM in particular has attracted much attention in recent years, and many access networks based on OFDM have been demonstrated [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Most of these experiments incorporated high-performing but costly optical components in the ONUs, such as lasers as local oscillators (LOs) for optical coherent detection at the ONU [18], or they used separate fibers for uplink and downlink [17][18][19][20][21]28], or EDFAs [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…A very interesting application of OFDM is Orthogonal Frequency Division Multiple Access (OFDMA), whereby different users are assigned to different OFDM subcarriers. Recently, OFDM/OFDMA has also been making its way into the optics world as well, with recent studies showing that OFDM/OFDMA can provide high capacity, long-reach and cost-effective operation for PONs [4], [5].…”
Section: Introductionmentioning
confidence: 99%